Sedimentary fluids/fault interaction during syn-rift burial of the Lodève Permian Basin (Hérault, France): An example of seismic-valve mechanism in active extensional faults. (December 2017) - Laurent, Dimitri; Lopez, Michel; Chauvet, Alain; Sauvage, Anne Charline; Buatier, Martine; Spangenberg, Jorge E.
Abstract: During basin burial, interstitial fluids initially trapped within the sedimentary pile easily move under thermal and pressure gradients. As the main mechanism is linked to fluid overpressure, such fluids play a significant role on frictional mechanics for fault reactivation and sediment deformation. The Lodève Permian Basin (Hérault, France) is an exhumed half-graben with exceptional outcrop conditions providing access to barite-sulfide mineralized systems and hydrocarbon trapped into syn-rift roll-over faults. Architectural studies show a cyclic infilling of fault zone and associated bedding-parallel veins according to three main fluid events during dextral/normal faulting. Contrasting fluid entrapment conditions are deduced from textural analysis, fluid inclusion microthermometry and sulfur isotope geothermometer. We conclude that a polyphase history of trapping occurred during Permian syn-rift formation of the basin. The first stage is characterized by an implosion breccia cemented by silicifications and barite during an abrupt pressure drop within fault zone. This mechanism is linked to the dextral strike-slip motion on faults and leads to a first sealing of the fault zone by basinal fluid mineralization. The second stage consists of a succession of barite ribbons precipitated under overpressure fluctuations, derived from fault-valve action. This corresponds to periodic reactivations of fault planes and bedding-controlled opening localized at sulphide-rich micro-shearing structures showing a normal movement. This process formed the main mineralized ore bodies by the single action of fluid overpressure fluctuations undergoing changes in local stress distribution. The last stage is associated with the formation of dextral strike-slip pull-apart infilled by large barite and contemporaneous hydrocarbons under suprahydrostatic pressure values. This final tectonic activation of fault is linked to late basinal fluids and hydrocarbon migration during which shear stress restoration on the fault plane is faster than fluid pressure build-up. This integrated study shows the interplay action between tectonic stress and fluid overpressure in fault reactivation during basin burial that clearly impact potential economic reservoirs. Highlights: Cyclic infilling of fault zone and bedding-parallel veins of MVT barite-sulphide mineralizations at a burial depth of 3 km. Fluid pressure fluctuations are deduced from vein texture, fluid inclusion microthermometry and isotope geothermometer. A multi-scale dynamic model for suction-pump and fault-valve action in sedimentary basin is proposed. We highlight the interplay action between tectonic stress and fluid overpressure for fault reactivation in the upper crust.